ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ РОЗВИТКУ РЕГІОНАЛЬНИХ РИНКІВ ПРАЦІ ШЛЯХОМ РОЗВ’ЯЗАННЯ ПРОБЛЕМИ ПІДГОТОВКИ КАДРІВ - Бородієнко , О.; Мільто, Л.; Каменська , І.; Бокшиц , О.; Малихіна , В. (Financial and credit activity problems of theory and practice, 2021)
Abstract. The purpose of the article is to highlight the problems of providing regional labor markets with qualified personnel and identify ways of effective interaction between educational institutions and enterprises. The theoretical significance of the article is that it, based on an experimental study conducted in the Donetsk region, analyzed the reasons for dissatisfaction of enterprises with the quality of professional training; the existing experience of cooperation between educational institutions and enterprises of the region is analyzed; barriers have been identified that prevent the establishment of an effective partnership between educational institutions and enterprises aimed at meeting the existing and future needs of the labor market in qualified personnel; the level of readiness of enterprises of the region to cooperate with institutions in the direction of modernization of material and technical base, internship of teachers, joint preparation of educational programs, advanced training of personnel is analyzed; on the basis of the analysis of results of survey it was identified professions for which it is advisable to start professional traininin in vocational institutions in Donetsk region; the model of competencies of the future skilled worker elaborated by employers is presented (on the example of the profession «Locksmith for repair of wheeled vehicles. Driver of motor vehicles (category «C»). Machinist of a truck crane»). The practical significance of the article is that based on the opinion of employers of Donetsk region, the authors offer recommendations to improve the interaction between educational institutions and enterprises of Donetsk region to solve the problem of professional training for current and future needs of the region’s economy. The presented recommendations and research model can be extrapolated to the effective development of labor markets in other regions of the country. It was revealed that the modern labor market in particular in Donetsk region is characterized by significant disparities between demand and supply of personnel (almost all vacancies in terms of occupations have a deficit, i.e. supply (number of unemployed) exceeds demand). There is a great lack of vacancies in the professions of auxiliary worker, driver of vehicles, seller of food products, seller of non-food products, cook. Instead, the scarce professions that are in demand in the labor market are a machinist bypassing turbine equipment, a locksmith repairing steam and gas turbine equipment, a machinist bypassing boiler equipment, an electrician servicing electrical installations, a kneading machine operator, a plumber, a nanny, an electrician for repair and installation of cable lines, a pipe and billet cutter, an extruder of refractory products. It is determined that the system of training of future skilled workers in educational institutions of the region needs significant modernization, as there are currently significant discrepancies between the level of preparation of graduates for professional activities and the requirements of employers. The difficulty of adaptation of graduates in the workplace is associated with the lack of certain professional competencies and personal qualities, the development of which should be paid attention to in the process of initial professional training in educational institutions — practical training, experience, practical knowlwdge), motivation to work. Deficits are also responsibility, independence, purposefulness, level of qualification. It was found that cooperation between educational institutions and employers is still carried out in traditional forms — the internships of students of educational institutions on the basis of enterprises, the participation of employees in assessing the quality of training. The prevalence of formal interaction significantly determines the quality of training for the needs of regional labor markets. The directions of personnel professional training for actual and perspective needs of the region labour market are singled out: excavator driver, car mechanic, electric gas welder, locksmith-repairman, electrician, turner, crane driver, confectioner cooker. The structure of the competency model of future skilled workers was identified — basic and professional competencies — that will ensure rapid adaptation and effective work of graduates at enterprises of the region. It is determined that for the effective development of regional labor markets and effective training for them the key is to implement the idea of public-private partnership of educational institutions and employers, the most effective forms of which should be cooperation in curricula development, advising on their content, methods and technologies of the educational process, providing recommendations for updating equipment, providing teaching materials, assistance in updating the library fund, databases, to ensure the educational process in the institution (invitation of so-called guest speakers), professional development of teachers and masters of industrial training, joint project activities, implementation of career guidance activities, organization of excursions of students and entrants to enterprises, informing about employment opportunities at enterprises, lobbying the interests of the institution at the level of local governments, participation in determining the development strategy of the institution, assistance in the process of attraction of additional sources of financing, creation of advisory bodies of the educational institution (advisory committee in the specialty, supervisory boards, etc.). Keywords: regional labor markets, professional training, educational institutions, institutions of professional (vocational) education, efficiency, professional training. JEL Classification I21, L33 Formulas: 0; fig.: 0; tabl.: 0; bibl.: 9.